2011
DOI: 10.1007/s00449-011-0640-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of S-adenosylmethionine (SAM) synthetase from Pichia ciferrii

Abstract: S-adenosylmethionine synthetase (SAM-s) catalyzes the synthesis of S-adenosylmethionine (SAM), which is essential for methylation, transcription, proliferation, and production of secondary metabolites. Here SAM-s from Pichia ciferrii were selectively cloned using RNA CapFishing and rapid amplification of cDNA ends (RACE). The putative full-length cDNA of SAM-s encoded a 383 amino acid protein (42.6 kDa), which has highly conserved metal binding sites, a phosphate-binding site, and functionally important motifs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Cysteine desulfurylase (spot 33), which catalyzes the formation of L-alanine from the substrate L-cysteine, is involved in the syntheses of many kinds of sulfur-containing biomolecules (Chen et al, 2012). S-adenosylmethionine synthetase [spot 30 (known as methionine adenosyltransferase)] is considered the rate-limiting step of the methionine cycle (Markham and Pajares, 2009) and catalyzes the formation of Sadenosylmethionine, which has been suggested to be essential for gene transcription, cell proliferation, and production of secondary metabolites (Yoon et al, 2012). Although it is well known that phenylalanine is required as a precursor for anthocyanins, there is little information on the effect of the amino acid metabolism on anthocyanin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine desulfurylase (spot 33), which catalyzes the formation of L-alanine from the substrate L-cysteine, is involved in the syntheses of many kinds of sulfur-containing biomolecules (Chen et al, 2012). S-adenosylmethionine synthetase [spot 30 (known as methionine adenosyltransferase)] is considered the rate-limiting step of the methionine cycle (Markham and Pajares, 2009) and catalyzes the formation of Sadenosylmethionine, which has been suggested to be essential for gene transcription, cell proliferation, and production of secondary metabolites (Yoon et al, 2012). Although it is well known that phenylalanine is required as a precursor for anthocyanins, there is little information on the effect of the amino acid metabolism on anthocyanin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…AdoMet metabolism is complicated by its interaction with plant growth hormones such as cytokinins and auxins [ 27 ]. Thus, AdoMet is involved in regulating plant developmental by fine-tuning gene transcription, cell proliferation, and the production of secondary metabolites [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAM acts as a transmethylator (transfers methyl groups from one molecule to another within a cell) or is involved in major biochemical reactions, such as gene transcription and expression, signaling, cell division and growth, and response to stress. Previous studies have also shown that overexpression of the SAM synthase gene or SAM-related genes in plants or eukaryotes increases tolerance to abiotic stress [ 14 - 20 ]. Therefore, in this study, we constructed and cultivated recombinant C. reinhardtii to overexpress the SAMS gene and investigate the cell growth and intracellular lipid accumulation under nitrogen-depleted or saline-stress conditions.…”
Section: Introductionmentioning
confidence: 99%